The Effectiveness of Critical Literacy Based Digital Learning Material (CL-DLM) to Increase Students’ Higher Order Thinking Skills at Elementary School - Nurhaedah Nurhaedah (Education Achievement: Journal of Science and Research, 2024)
This research aimed to develop Thematic critical literacy based digital teacing materials (TCL-DLM) to increase students’ higher order thinking skills at elementary school. This research is a research development with a 4-D model (define, design, develop, and dissemination). Data collection techniques were carried out through teaching material validation sheets, teacher response questionnaires, student response questionnaires, learning implementation observation sheets and tests of higher order thinking skills. The data obtained were analyzed descriptive quantitative. The results of the study show that: 1) The results of the needs analysis are that thematic learning is still limited to the use of teaching materials in the form of theme books and electronic books that have been prepared by the government so that it is necessary to develop practical and effective teaching materials. The students’ higher order thinking skills based on pretest dominated in medium category (51.85%). 2) The development of these teaching materials uses the Four-D teaching material development procedure from Thiagarajan which consists of the defining, designing, developing, and disseminating stages, 3) Thematic critical literacy based digital learning material (TCL-DLM) have met the validity criteria, because the results of validation from material experts and the learning design of teaching materials is in the very valid category (M = 3,82), 4) Thematic critical literacy based digital learning material (TCL-DLM) is in the effective category because there is an increase in the results of tests of higher-order thinking skills after the application of Thematic critical literacy based digital learning material (TCL-DLM) in class VI students of SD Telkom Makassar. Postest category dominated in very good category (81.48%). In addition, teachers and students expressed a positive response. 5) Thematic critical literacy based digital learning material (TCL-DLM) is also in the practical category because it has been well implemented which includes the criteria of ease of use, time efficiency and very practical benefits. The recommendation of this research is Thematic critical literacy based digital learning material (TCL-DLM), needs more developed both in terms of material and features of digital teaching materials and more interesting so students' higher-order thinking skills can be better.